Pediatric dentists’ preference on usage of hand files or rotary files for pulpectomy of primary molars - A retrospective study - Akshaya K,; Vignesh Ravindran,; Senthil Murugan Pandurangan, (International Journal of Research in Pharmaceutical Sciences, 2020)
Dental caries is the most prevalent chronic condition of the oral cavity. Excessive tooth decay can inflame pulp requiring pulpal intervention. One such endodontic procedure done to treat pulpitis is pulpectomy which is defined as complete removal of coronal and Radicular pulp. It can be done through hand or rotary filing techniques. A rotary filing system is better over hand filing that it gives more conical canal, reduces preparation time and thus enhances child cooperation. To analyse the preference of pediatric dentists in a private dental institution in using rotary and hand filing techniques during pulpectomy procedures in primary molars. All the cases reported between the month of June 2019 to March 2020 for pulpectomy in primary molars in paediatric patients were chosen for this study. Data of pediatric patients who underwent pulpectomy were shortlisted and the instrumentation techniques used were analyzed, tabulated and was subjected to statistical analysis. From the statistical analysis, it can be analysed that paediatric dentists had a higher preference towards rotary filing technique (85.7%), predominantly in male patients (57.2%) between the age group of 2 to 5 years (67%), primarily in mandibular molars (67.1%). Within the limitation of this study, the commonly preferred instrumentation technique by paediatric dentists for pulpectomy of primary molars is rotary over hand filing.